2021
DOI: 10.1002/ejic.202100232
|View full text |Cite
|
Sign up to set email alerts
|

Easily Prepared Mono(N,N‐dialkylamino)phosphine Palladium(II) Complexes: Structural and Catalytic Evaluation

Abstract: The search for efficient, active and universal catalyst systems for transition-metal catalyzed cross-coupling reactions, continues to be of interest to researchers world-wide. Herein, we report two new Pd(II) complexes, effortlessly prepared from N,Ndialkylamino-phosphines for Suzuki-Miyaura cross-coupling reactions. These sufficiently hindered (% V Bur = 30.0-31.5 %) and electron rich (v CO = 1947.41-1946.29 cm À 1 ) aminophosphines formed active catalysts for Suzuki-Miyaura coupling of aryl bromides and chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it was concluded that the biphenyl ligands sterically shield the phosphorus atom which was confirmed by single-crystal X-ray analysis (see Section 2.2). The phenyl derivative of bis(biphenyl)diisopropylamino phosphine is widely used as ligand for transition-metal catalyzed cross-coupling reactions [31][32][33] or for coordination chemistry [34,35].…”
Section: Scheme 3 Synthesis Of the Bis(biphenyl-2-yl)-nn-diisopropylphosphanamine Bmentioning
confidence: 99%
“…Therefore, it was concluded that the biphenyl ligands sterically shield the phosphorus atom which was confirmed by single-crystal X-ray analysis (see Section 2.2). The phenyl derivative of bis(biphenyl)diisopropylamino phosphine is widely used as ligand for transition-metal catalyzed cross-coupling reactions [31][32][33] or for coordination chemistry [34,35].…”
Section: Scheme 3 Synthesis Of the Bis(biphenyl-2-yl)-nn-diisopropylphosphanamine Bmentioning
confidence: 99%